Analysis of Office Facilities Management in Enhancing Employee Job Satisfaction at the National Brain Center Hospital - Hana Dizamira Morgen Morgen; Christian Wiradendi Wolor (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This descriptive qualitative study aims to analyze office facility management at the National Brain Center Hospital (RSPON) and its role in enhancing employee job satisfaction within the ULP and PPK units. Data were collected through structured interviews with four participants, direct observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that while facility management is well-structured through the EMISY digital system, challenges remain regarding uneven distribution, suboptimal ergonomics, and unplanned hardware upgrades. Drawing on Herzberg’s two-factor theory, office facilities—particularly computers and internet connection—function as hygiene factors, meaning their deficiencies directly cause job dissatisfaction. Therefore, this study recommends developing data-driven asset management, upgrading ergonomic standards, and ensuring equitable facility distribution across all work units.